DATA VISUALIZATION AND DEPICTION INTERFACE TO DEVELOP CANCER EPIDEMIC DATASET - D. Roja Ramani,; Sundar, G.Naveen; N.Bhuvaneswary,; D.Narmadha,; P.Nagaraj, (International Journal of Psychosocial Rehabilitation, 2020)
Data visualization is the vivid depiction of information and data. By using visual elements like charts, graphs, and maps, data visualization tools provide a versatile way to glimpse and understand trends, outliers, and patterns in data. In the world of Big Data, data visualization tools and technologies are vital part of analyzing the massive amounts of information and make data-driven decisions. As an outcome of the progressive technological trend, massive amounts of data from different subjects and areas are continuously generated and classified on a daily basis. In the past, the main problems were the preservation and publishing of data sets, but today, one of the main challenges is the presentation for more understanding of the data. The suitable visual representation of a given data set is the foundation for a precise and consistent interpretation, analysis and adoption of empirical conclusions related to the semantic meaning of information. In this paper, we present a synopsis of data visualization techniques and their practical application, starting from the acquisition of an unstructured set of publicly available data, their proper preprocessing and organization, and the visual representation for the end user. The nature of the data is related to the emergence, potential and development of various types of cancer diseases officially registered in different geographical regions. We present an interactive system that implements several visualization techniques.